H(2) Production by Selenomonas ruminantium in the Absence and Presence of Methanogenic Bacteria - Scheifinger, C. C. (1975)
Selenomonas ruminantium is a nonsporeforming anaerobe that ferments carbohydrates primarily to lactate, propionate, acetate and CO(2). H(2) production by this species has not been previously reported. We found, however, that some strains produce trace amounts of H(2) which can be detected by sensitive gas chromatographic procedures. H(2) production is increased markedly, in some cases almost 100-fold, when the selenomonads are co-cultured with methane-producing bacteria. Growth of the methane-producing bacteria depends on H(2) production by the selenomonads and the subsequent use of H(2) for the reduction of CO(2) to CH(4). Although no free H(2) accumulates in the mixed cultures, the amount of H(2) formed by the selenomonads can be calculated from the amount of methane produced. These studies indicate that the conventional methods for measuring H(2) production by pure cultures do not provide an adequate estimate of an organism's potential for forming H(2) in an anaerobic ecosystem where H(2) is rapidly used, e.g., for formation of CH(4).